Engaging People in Implementing Lean Manufacturing: An Analysis of the Rolls- Royce Production System - Ford, Martin (2015)
Purpose: Lean manufacturing has been widely adopted by manufacturing organisations across the world over the last thirty years with varying level of success. With some organisations failing to deliver any benefit from it there has been extensive research into why. This research paper reviews the current state of lean manufacture and the issues organisations have been experiencing when implementing their version of lean manufacturing. Focusing specifically on how well the organisations are engaging their people in the implementation, it analyses Rolls- Royce‘s implementation of their latest lean manufacturing initiative- the Production System.